Искусство и творческая активность масс - Левчук Л. Т. Лариса Тимофеевна; Шангин С. Н. Сергей Николаевич; Канарский А. С. Анатолий Станиславович (Киев, Вища школа, 1985)
Авт. указаны на обороте тит. л.